2015
DOI: 10.1590/0102-311x00010014
|View full text |Cite
|
Sign up to set email alerts
|

La mala calidad de sueño se asocia a una menor adherencia al tratamiento antirretroviral de gran actividad en pacientes peruanos con infección por VIH/SIDA

Abstract: Con el objetivo de evaluar si existe asociación entre la mala calidad de sueño y la adherencia al tratamiento antirretroviral de gran actividad (TARGA) en personas con infección por VIH/ SIDA; llevamos a cabo un estudio analítico de corte transversal que incluyó 389 pacientes peruanos en TARGA. La mala calidad de sueño fue medida con la Escala de Calidad de Sueño de Pittsburgh y la adherencia con el CEAT-VIH. Realizamos un modelo lineal generalizado de familia Poisson, con errores estándar robustos para estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
6
0
4
Order By: Relevance
“…The flow diagram of study selection is shown in Figure . Fifty‐three studies, composed of 22,603 participants in ART from 25 LAC countries, met eligibility criteria for the systematic review (Table ) . The median number of participants in ART per study was 201 [range: 13 – 3343; interquartile range (IQR): 394 – 125].…”
Section: Resultsmentioning
confidence: 99%
“…The flow diagram of study selection is shown in Figure . Fifty‐three studies, composed of 22,603 participants in ART from 25 LAC countries, met eligibility criteria for the systematic review (Table ) . The median number of participants in ART per study was 201 [range: 13 – 3343; interquartile range (IQR): 394 – 125].…”
Section: Resultsmentioning
confidence: 99%
“…Em outros países onde o CEAT-VIH também foi utilizado, e apesar de apresentarem características distintas, os resultados mostraram-se próximos ao deste estudo quanto à avaliação da adesão. Na Romênia e na Colômbia, a adesão estrita foi descrita em 15% da população estudada, todavia, no Peru, o percentual aumentou para 25,5% [14][15][16] . , v. 11, n. 2, p. 307-314, maio/agosto 2018 -ISSN 1983-1870 -e-ISSN 2176-9206 Assim, por a adesão ser considerada um processo multifatorial, dinâmico e variável, e estar implicada a um conjunto de características e ações que podem ou não interferir na ingestão dos medicamentos antirretrovirais, ressalta-se a importância dos serviços de saúde em realizar constantemente a avaliação da adesão 7 .…”
Section: Discussionunclassified
“…Outro fator que dificulta a adesão é o fato de as pessoas realizaram esforços ou de até que ponto se sentem capazes de seguir o tratamento. As pessoas que necessitam realizar um esforço maior para realizar o tratamento acabam, por vezes, não o realizando adequadamente 16 . Além disso, o apoio insuficiente do meio social e familiar parece afetar negativamente a adesão, encaminhando o paciente à depressão e à desesperança.…”
Section: Discussionunclassified
“…Poor sleep quality is associated with several adverse consequences in the HIV-infected population. These consequences include impact on ART adherence, decreased engagement in HIV-care, diminished health-related quality of life, excessive daytime sleepiness, and cognitive impairment (Tedaldi, Minniti, & Fischer, 2015;Tello-Velasquez et al, 2015;Vosvick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%